Identifikasi Persepsi Mahasiswa Tentang Sistem Pembelajaran Keterampilan Medik Pemasangan Kateter Urin di Fakultas Kedokteran Universitas Mataram - Mujahidin Irham, Achmad; Maulana , Akhada; Zuhan, Arif (CV RIFAINSTITUT, 2022)
Mastery of students in medical skills is a very important aspect that will bridge the gap between clinical competence and procedural knowledge. Based on the 2012 Indonesian Doctor Competency Standards, urinary catheter installation skills have 4A competencies, which means that a primary care doctor graduate must be able to do it independently, by mastering theory, indications, contraindications, and complications that can arise. Students' perceptions of the learning system and learning environment will be the basis for maximizing and varying the learning system and environment. Basic knowledge of students related to a learning system will affect the perception and how the student learning process in the future. This research is a descriptive study with a research design cross sectional for students in the fifth and seventh semesters of the Medical Education Study Program, Faculty of Medicine, University of Mataram. The sampling technique used a total sampling technique and the sample was asked to fill out a questionnaire about perceptions of medical skills in inserting a urinary catheter. From 196 respondents consisting of men (34.7%) and women (65.3%) with an age range of 19-23 years. Good perception of medical skills in infusion is seen from the percentage of motivation factors (96.9 %), instructors (89.8%-100%), self-awareness (99%-100%), learning atmosphere (81.1%-96 .9%), facilities and infrastructure (43.4%-89.3%), self-confidence (57.7%-99.5%), and clinical learning environment (89.8%). The bad perception is only found in the difference between learning in the mannequin and the patient (56.6%). The majority of students have a good perception of the medical skills learning system of urinary catheter insertion.